KEMAMPUAN MENULIS PARAGRAF EKSPOSISI DENGAN MENGGUNAKAN MEDIA GAMBAR SISWA KELAS X SMA NEGERI 2 LUBUK SIKAPING - Putri, Septia Tania; Chan, Wirsal; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2014)
To write the exposition is the one of the writing skills that should be taught in the school. In the fourtu competency standard in KTSP can be found about learning of writing, which express many informations in some paragraphs form like (narrative, descriptive, exsposition). The research problem is limited to the ability to write a paragraph of exposition by using media images tenth grade students of SMA Negeri 2 Lubuk Sikaping terms of aspects (1) to provide knowledge in accordance with the object (image), (2) answer the question, (3) using a standar language, (4) does not affect the reader. This type of research is a quantitative study using descriptive methods. Perindicators data research results are as follows. (1) provide knowledge in accordance with the object (image) is more than enough qualifications (73,8%), (2) answer questions more than enough qualificationÂ  (75,1%), (3) using both standard language qualification (84,5%), (4) does not affect either all qualified readers (89,4%). Based one the analysis of these data it can be concluded that the ability to write a paragraph of exposition by using the media image class X SMA Negeri 2 Lubuk Sikaping classified as good (80,7%).